Perubahan Fungsi Ruang pada Cultural Landscape Subak di Perkotaan: Studi Kasus Subak Padang Galak Kota Denpasar - Suryada, I Gusti Agung Bagus (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023, 2023)
Changes in Spatial Functions in Subak Cultural Landscape in Urban Areas: A Case Study of Subak Padang Galak City of Denpasar. The Subak cultural landscape is a world cultural heritage that has an important meaning for the people of Bali and the world, so it needs to be preserved. Changes in the cultural landscape in urban areas are inevitable due to urban development. The cultural landscape of Subak Padang Galak is a subak in the city of Denpasar that efforts have been made to preserve. Conservation efforts have been carried out by the Denpasar City government and the Kesiman Kertalangu Village administration. Conservation efforts are also carried out by the private sector by developing tourist attractions. The presence of new activities in the subak area will change the function of the space. To minimize the negative impact due to new activities in the subak area, it is necessary to study the changes in spatial function that occur in the Padang Galak subak. This research is a qualitative research. The analysis was carried out using a comprehensive literature review which was carried out by comparing objects with concepts or theories descriptively. The results of this study indicate that in addition to agricultural functions in the subak area, there are also recreational functions, sports functions, economic functions, communication functions and service functions. In general, the new function is still in accordance with city zoning regulations.